Analysis of the long song “Barga gurvan bor” - Gempil, Setsen; Delgerkhuu, Narantsatsral (Mongolian Journal of Arts and Culture, 2025)
Folk songs reflect society, nature, people’s lives, history of struggles, their ideals and behaviors. Folk songs of the Barga Mongolians are an intangible cultural heritage that they composed and passed down from generation to generation. Barga folk songs reflect the rituals of the Barga people, including herding culture, household culture, historical events, historical people, religion, ideals, and weddings. There is a concentration of thought that favors sunset. When talking about the long songs of the Barga people, it is necessary to mention the three bors of Barga. Er bor hartsaga, Soyog bor, Bor bor byalzuuhai, which are popularly known as the three bors of Barga, are called songs to cheer people up. These songs are the roots of barga folk songs. We aimed to examine these songs from several aspects, including style, subject matter, continuity of tradition, and singing style. The main feature is that they are different from the khalkh and borjigon versions in terms of their tone, and that they have a lot of ornamentation at the beginning of the song that suits their dialect characteristics, and that they often end their songs with a khayal, which is usually a minor style of long songs. However, the example of the singer’s personality and creativity is an example of the legacy of the singer Myagmarsuren. He sang the vowels with a large vowel, which made the barga urtyn song richer and broader. The characteristics of the above three songs, including the structure of the melody, intonation, and ornamentation, were analyzed musically. “Баргын гурван бор” уртын дуунд хийсэн шинжилгээ Хураангуй: Ардын дуунд нийгэм, байгаль, ард түмний амьдрал тэмцлийн түүх, тэдний үзэл баримтлал, зан үйл зэргийг тусгаж байдаг. Барга монголчуудын ардын дуу бол өөрсдөө зохион дуулж, үеийн үед өвлөн уламжлуулсан биет бус соёлын өв билээ. Барга ардын дуунд баргачуудын мал маллах соёл, ахуйн соёл, түүхэн үйл явдал, түүхт хүмүүс, шашин шүтлэг, үзэл баримтлал, хурим найрыг багтаасан зан үйлийн талаар тусгасан байдаг бөгөөд нутаг усаа тахиж, өвөг дээдсээ хүндэлж, үр хүүхдээ энхрийлэн, энх амгаланг хүсэж, бүгдээр жаргахыг эрхэмлэдэг сэтгэлгээний төвлөрөл оршдог. Барга уртын дууны тухай өгүүлэхэд Баргын гурван борын тухай заавал дурдах хэрэгтэй. Баргын гурван бор гэж алдаршсан “Эр бор харцага”, “Соёг бор”, “Бор бор бялзуухай”-г хүмүүс хийморь сэргээх дуу гэдэг. Эдгээр дуу бол барга ардын дууны сор нь юм. Дуунуудыг бид хэв шинж, сэдэв агуулга, уламжлал залгамж чанар болон дуулах хэв маяг зэрэг хэд хэдэн талаас авч үзэхийг зорьсон. Гол онцлог нь аялгууны царааны хувьд халх, боржигон хувилбараас ялгаатай, хэл аялгууны онцлогтоо тохирсон дууны эхлэл чимэг ихтэйгээс гадна дуугаа ихэвчлэн хаялгаар төгсгөдөг, ихэвчлэн уртын дууны бэсрэг хэв шинжид хамаарна. Гэхдээ дуучны онцлог, бүтээлч чанар нөлөөтэй болохыг өвлөн уламжлагч Мягмарсүрэнгийн жишээ харуулж байна. Тэрээр эгшгийг томж дуулсан нь барга уртын дууг улам баялаг, өргөн болгожээ. Дээрх гурван дууны онцлог, аялгууны бүтэц, эгшиглэгээ, чимэглэл зэрэгт хөгжмийн шинжилгээ хийлээ. Түлхүүр үгс: Бор бор бялзуухай, Эр бор харцага, Соёг бор, домгийн судалгаа, хөгжмийн шинжилгээ